Rail shear testing / Ubaidillah Ambiah - Ambiah, Ubaidillah (2002)
In this project, we are interested to design a new fixture for shearing test method that uses a thin plate a test specimen. We found that the idea has already been practiced in ASTM D4255/D4255M-83 (Reapproved 1994). Since the method was almost the same, but the test fixture was a modified version, we agreed to follow the ASTM D4255 standard as a reference. In this project modifications on the test fixture are done. This project consists of the design concept including the design process and fabrication of the rail shear test fixture. An analysis step that is part of design is described and the experimental results using the newly modified fixture are also discussed. The comparison has been made between the modified fixture and the ASTM method.